The Implementation of Hadith Tarbawi in Students' Character Development: A Phenomenological Study of SDIT Tiara Islamic School - Syahruddin Srg (Madako Elementary School, 2026)
The decline of moral values, including honesty, discipline, and responsibility, has become a critical issue in education. This study aims to analyze the implementation of Hadith Tarbawi in fostering students’ character at SDIT Tiara Islamic School. The investigation focuses on its application in Islamic Religious Education, teachers’ instructional strategies, supporting and inhibiting factors, and its contribution to students’ character development. A qualitative case study approach was employed. Data were collected through semi-structured interviews, classroom observations, and document analysis involving Islamic Religious Education teachers, the principal, and homeroom teachers. Data were analyzed through condensation, data display, and conclusion drawing. The findings reveal that Hadith Tarbawi was implemented through classroom instruction, teacher role modeling, habituation, and the cultivation of a religious school culture. Teachers applied exemplary practices, narratives of the Prophet Muhammad SAW (peace be upon him), discussions, experiential learning, and reward-based reinforcement to develop students’ religious commitment, honesty, discipline, politeness, responsibility, compassion, and cleanliness. Successful implementation was supported by teachers’ commitment, effective school leadership, religious programs, and parental involvement. However, challenges included excessive gadget use, limited character habituation at home, time constraints, and students’ diverse characteristics. School–family collaboration emerged as the cornerstone of strengthening Tarbawi Hadith based character education.